Raymund Schwager on the Dramatic Justice and Mercy of God: Justice and Mercy of God - Brown, Benjamin (International journal of systematic theology, 2015)
This article explores and develops Raymund Schwager's understanding of the nature of justice and mercy, especially in the face of the Christian doctrine of hell. Schwager follows Anselm of Canterbury closely in seeing a deep harmony between justice and mercy, finding their unity in an expansive notion of God's goodness, which gives abundantly but always also in a way that respects the dignity of the receiver. This unity can thus only be understood in the context of the dramatic interplay of freedoms. An overview of Schwager's theological project provides the background for then exploring his notions of justice, mercy, freedom, self-judgement and hell. The article concludes with the exploration of some of the logical consequences of Schwager's thought.